(untitled) (Research, Society and Development, 2022)
The aim of the article is a systematic review and bibliometric analysis on the topic of hospital performance indicators, with validation of indicators found in the literature with specialists and managers in the area through the use of the adapted DELPHI method. Indicators are important tools for analyzing hospital performance. Defining these indicators is not always a simple job for decision makers. The systematic review of the literature through bibliometric analysis offered a first step in this definition of indicators, which was analyzed using the bibliometric analysis package Bibliometrix for R. Followed by validation using the DELPHI method adapted for the online and asynchronous one-step environment methodological important to this study, which achieved the consensus of a group of experts on which hospital indicators should be considered essential in the assessment of quality and performance, consolidating as a result of the study a total of 11 essential indicators for the analysis of hospital performance.